Shifting gears to differentiation agents in acute promyelocytic leukemia with resource constraints—a cohort study. (2nd September 2022) - Vaid, Tejasvini; Aggarwal, Mukul; Dass, Jasmita; Dhawan, Rishi; Kumar, Pradeep; Viswanathan, Ganesh Kumar; Tyagi, Seema; Seth, Tulika; Mahapatra, Manoranjan
Abstract: Background: Treatment of acute promyelocytic leukaemia has emerged as a major success in hemato-oncology. While literature from the developed world boasts of outstanding outcomes, there is a paucity of data from the developing world. This study aimed to assess complications and outcomes of acute promyelocytic leukaemia in a resource-constrained setting. Methods: We retrospectively collected data from patients diagnosed with APL from January 2016 to December 2020. Results: Sixty-four patients were treated-32 in both the Sanz high and low-risk groups. In the Sanz low-risk group, 12.5% of patients received ATRA with daunorubicin and 81.25% received ATRA with ATO. In the Sanz high-risk group, 18.8% of patients received ATRA with daunorubicin, 34.3% received ATRA with daunorubicin and ATO while 40.6% received ATRA with ATO. 56.25% of patients developed differentiation syndrome. The incidence was higher in Sanz high-risk group as compared to Sanz low-risk group. 57.4% of patients had an infection at the time of presentation. 62.5% of patients developed neutropenic fever during treatment. 17.2% of patients developed pseudotumor cerebri. The 4-year EFS and OS were 71.25 and 73.13%, respectively. Sanz low-risk group had a better 4-year EFS and OS as compared to the Sanz high-risk group. Haemoglobin at presentation and Sanz high-risk group were associated with poorer outcomes with a hazard ratio of 0.8 and 3.1, respectively. Outcomes in high-risk patients were better with the use of ATRA + ATO + daunorubicin. Conclusion: In the Indian population, APL patients have a high incidence of differentiation syndrome, pseudotumor cerebri, and infections during induction. CR, EFS, and OS compared to the developed world can be achieved with optimal therapy. Low haemoglobin at presentation and Sanz high-risk group were associated with poorer outcomes. ATRA, ATO, and daunorubicin combination is the preferred protocol for treating high-risk patients.